Influence of Memorable Culinary Experience on Revisit Intention Mediated by Place Identity in Semarang - Kodriyah, Laela; Putra, Harmanda Berima (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
This research aims to examine the influence of memorable culinary tourism experiences on revisit intention directly and indirectly through the mediating role of place identity. The research method used is a quantitative method. A sample of 162 people was obtained through the use of a purposive sampling method which took into account certain characteristics in the collection process. The data collection technique in this research is a questionnaire in the form of a Google Form. data analysis using Structural Equation Modeling Smart PLS. The results showed that a memorable culinary tourism experience has been proven to have a positive influence on place identity, however, place identity has not been proven to have a positive influence on revisit intention and there is no proven mediating role for place identity.